Venturing into the sea at dawn - Mumbai Archive Project Team (Jio Institute, 2024)
Koli fishermen venture to sea when it is still dark, usually around 5 am, taking advantage of the high tide and reaching their netting points before sunrise. The tide plays a crucial role as fewer fish are caught during low tide, while high tide brings an abundant catch.